Toward Routine Minimally Invasive Ventricular Septal Defect Closure Via Right Lateral Minithoracotomy - Aydin, Selim; Temur, Bahar; Basgoze, Serdar; Guzelmeric, Fusun; Guvenc, Osman; Erek, Ersin (Frontiers in Pediatrics, 2021)
Background: Improving the surgical results and recent advancement of transcatheter techniques for closure of ventricular septal defect (VSD) increased the demand for minimally invasive approaches. In this study, we analyzed the results of the patients who underwent VSD closure with right lateral minithoracotomy (RLMT). Methods: Between September 2014 and February 2021, 24 patients underwent minimally invasive VSD closure with RLMT. The median age of the patients was 16 months (range, 4-84 months). Fifteen patients (62.5%) were female. The median weight of the patients was 9.75 kg (range, 4.6-30 kg). The types of VSD were perimembranous in 19 patients, subaortic in three patients, inlet in one patient, and subpulmonic in one patient. Five patients had low-lying pulmonary stenosis in addition to VSD. Results: No perioperative death or major complication occurred during follow-up. All defects were repaired through RLMT. The median cardiopulmonary bypass time was 81 min (range, 44-163 min), and the aortic cross-clamp time was 65 min (range, 33-131 min). The median hospital stay was 6 days (range, 5-21 days). One patient had minimal (2 mm) residual left-to-right shunt. All families were satisfied with the cosmetic results during the follow-up. Conclusions: The RLMT method is a safe and effective alternative to standard median sternotomy for VSD closure and can be performed with favorable cosmetic and clinical results.